Age- and sex-specific incidence of non-traumatic lower limb amputation in patients with type 2 diabetes mellitus in a U.S. claims database. (November 2020) - Gandhi, Sampada K.; Waschbusch, Max; Michael, Madlen; Zhang, Meng; Li, Xinyu; Juhaeri, Juhaeri; Wu, Chuntao
Highlights: Incidence of non-traumatic LLA in males was higher compared to females in patients with type 2 diabetes mellitus (T2DM). The incidence of all LLA increased with an increasing age among patients with T2DM. Males and older patients with T2DM at higher risk of developing LLA in the US, warranting further exploration of risk factors in these subgroups. Abstract: Aim: To estimate age- and sex-specific incidence rates (IRs) of non-traumatic lower limb amputations (LLA) in patients with type 2 diabetes mellitus (T2DM) using a claims database from the United States (US). Methods: Patients with T2DM 18 years and older were identified using the Truven Health MarketScan database from January 1, 2007 to September 30, 2018. The overall and age- and sex-specific IRs of all non-traumatic LLA, minor LLA (amputation at or below the ankle), and major LLA (amputation above ankle) were calculated. Results: Among the 6, 117, 981 patients with T2DM, 14, 627 LLA events occurred (minor LLA; 72.8%; major LLA: 27.2%). The IRs (95% CI) of all LLA, minor LLA, and major LLA per 1000 person-years or PY were 0.86 (0.85, 0.88), 0.63 (0.62, 0.64), and 0.23 (0.23, 0.24), respectively. The IR (95% CI) of all LLA per 1000 PY in males was higher compared to females [1.24 (1.22, 1.26) vs. 0.46 (0.45, 0.48)]. The incidence of all LLA increased with an increasing age (highest IR in age-group of ≥80 years). Conclusions: This study identified males and older patients with T2DM at higher risk of developing LLA in the US, warranting further exploration of risk factors of LLA in these subgroups.